Comparison of the Quality of Life of Addicts Participating in Either Narcotics Anonymous or, Therapeutic Community Group Sessions or Receiving Methadone-Therapy a Cohort Study in Mashhad in 2013 - Hamid Bazazkahani; Amirreza SalehMoghaddam; Saeed vaghee; Andishe Hamedi (Shahid Sadoughi University of Medical Sciences, 2022)
Background: Chronic and prolonged illnesses and disorders, such as addiction, lead to a crisis in the lives of people with disabilities and can lead to a decrease in their quality of life. Therefore, in this study, we decided to compare the quality of life of individuals with substance use disorders who participate in Narcotics Anonymous, therapeutic Community session with Methadone-treated groups. Methods: This cohort study was conducted on detoxified patients attending Narcotics anonymous, therapeutic community sessions and Methadone-treated place. Quality of life of subjects measured at baseline and 1.5 months after the start of treatment. Data were analyzed by SPSS19 software using ANOVA, paired t-test, Chi-square analysis. Results: The mean score of quality of life between three groups was not significantly different at the beginning of the study, but the mean score of quality of life among individuals with substance use disorders participating in the sessions of Narcotics anonymous and therapeutic community group increased significantly (P <0.001) 1.5 months after the start of treatment. Conclusion: The results of this study indicate that the presence of detoxified persons in sessions of Narcotics anonymous and therapeutic community was effective in improving their quality of life. However, this effect is greater in Narcotics Anonymous. Therefore it was suggested that individuals with substance use disorders participate in these meetings.